USE OF MCMASTER PLUS FOR UPDATING SYSTEMATIC REVIEWS - Athale, Abha (My University, 2015)
Background Systematic reviews (SRs) of treatment effect are evidence syntheses that inform clinical practice decisions and healthcare policy. To maintain validity, SRs should be regularly updated to include novel research. In reality, updating practices are irregular, with resource and time constraints often cited as major barriers. The McMaster Premium LiteratUre Service (PLUS) is a database of high quality, pre-appraised evidence, which may be of potential help in efficient updating of SRs. Objective To determine the utility of McMaster PLUS to increase the efficiency of systematic review updating Methods Updated Cochrane reviews published from January 2012-January 2013 with changed conclusions were identified. Using the PubMed IDs of references in the updated review, which were not present in the previous version, we looked for the presence of these references in the PLUS database. Further, using Clinical Query (CQ) filters on PubMed, we identified the references not found in PLUS. Results Eight hundred fifty-four unique trials, reported in over 1498 references were used to drive a change in conclusion in the 92 included reviews. Of the 854 unique trials, 180 (21.1%) were found in the PLUS database. All of the newly added trials were in PLUS for 8 of 92 reviews, and none of the newly added trials were in PLUS for 26 of 92 reviews. Of the 834 references not found in PLUS, there were 728 unique PubMed IDs. Using the sensitive CQ filter, 701 (96.2%) of these trials were identified. Conclusion PLUS included 21.1% of trials used to drive a change in conclusion in 92 Cochrane reviews. Furthermore, the CQ filters performed admirably in the retrieval of articles not found in PLUS. These alternate search methods should be considered when updating SRs to help increase the efficiency of the update process. These methods should be further tested prospectively.